2015
DOI: 10.1038/nature14564
|View full text |Cite
|
Sign up to set email alerts
|

Large heterogeneities in comet 67P as revealed by active pits from sinkhole collapse

Abstract: Pits have been observed on many cometary nuclei mapped by spacecraft. It has been argued that cometary pits are a signature of endogenic activity, rather than impact craters such as those on planetary and asteroid surfaces. Impact experiments and models cannot reproduce the shapes of most of the observed cometary pits, and the predicted collision rates imply that few of the pits are related to impacts. Alternative mechanisms like explosive activity have been suggested, but the driving process remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(142 citation statements)
references
References 39 publications
8
133
1
Order By: Relevance
“…The Seth region also contains a number of circular pits. The largest is 210 m in diameter, ∼170 m deep, and shows evidence of dust emission from depth (Thomas et al 2015;Vincent et al 2015). Layering is also evident in Seth, in some cases, partially buried under a dusty cover (see Massironi et al 2015).…”
Section: Sethmentioning
confidence: 99%
See 1 more Smart Citation
“…The Seth region also contains a number of circular pits. The largest is 210 m in diameter, ∼170 m deep, and shows evidence of dust emission from depth (Thomas et al 2015;Vincent et al 2015). Layering is also evident in Seth, in some cases, partially buried under a dusty cover (see Massironi et al 2015).…”
Section: Sethmentioning
confidence: 99%
“…The acronyms in the header columns correspond to the following respectively: collapsing material (CM), cratered cones/Pancake-shaped mounds (CC/P-SM), smooth deposits (SD), and dust/airfall (D/A). Finally, the locations of active pits are from Vincent et al (2015).…”
Section: Regional Morphologymentioning
confidence: 99%
“…It is therefore likely that a population of cm-sized grains would have been injected into the dust coma in this time period under normal condition. On the occasions of large outbursts as often seen between 2015 July and September, that might have been generated by thermal stress and/or cliff collapse (Vincent et al 2015(Vincent et al , 2016, particles of even metre-size could be ejected (Pajola et al 2015). The validity of this approximation depends on the radiative cooling process of the nucleus surface as examined by Sekanina (1988Sekanina ( , 1992.…”
Section: The Dust Motionmentioning
confidence: 99%
“…The close-up observations of the coma activities and surface morphology by the remote-sensing instruments and a suite of in situ experiments as the comet moved around its perihelion point provided a wealth of information on the basic E-mail: ianlai@g.ncu.edu.tw properties of the sublimation-driven erosion of this short-period comet (Keller et al 2015;Sierks et al 2015;Vincent et al 2015). Of particular importance is the transport of dust material across the nucleus surface as it has significant effects on the short-term and long-term evolution of the outgassing behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its small dimensions, ∼4 km in diameter, 67P shows a wide morphological diversity: enveloping strata (Massironi et al 2015), pits (Vincent et al 2015), boulders (Pajola et al 2015), high-reflectivity boulder clusters (Pommerol et al 2015), local fracturing (El-Maarry et al 2015), as well as dust covered terrains (Thomas et al 2015b) are only some notable features which can be found on 67P.…”
mentioning
confidence: 99%